2004
DOI: 10.1038/sj.emboj.7600370
|View full text |Cite
|
Sign up to set email alerts
|

Supraphysiological nuclear export signals bind CRM1 independently of RanGTP and arrest at Nup358

Abstract: Leucine-rich nuclear export signals (NESs) mediate rapid nuclear export of proteins via interaction with CRM1. This interaction is stimulated by RanGTP but remains of a relatively low affinity. In order to identify strong signals, we screened a 15-mer random peptide library for CRM1 binding, both in the presence and absence of RanGTP. Under each condition, strikingly similar signals were enriched, conforming to the NES consensus sequence. A derivative of an NES selected in the absence of RanGTP exhibits very h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
110
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(119 citation statements)
references
References 59 publications
7
110
1
1
Order By: Relevance
“…1, B and C). We have previously shown that depletion of Nup358 causes a small reduction in export of a Rev(1.4)-GFP-NES reporter protein (43), which is targeted to the cytoplasm and sensitive to leptomycin B (44,49). In addition to an NLS, the Rev(1.4) protein also provides nuclear retention activity which permits a more stringent assessment of nuclear export.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1, B and C). We have previously shown that depletion of Nup358 causes a small reduction in export of a Rev(1.4)-GFP-NES reporter protein (43), which is targeted to the cytoplasm and sensitive to leptomycin B (44,49). In addition to an NLS, the Rev(1.4) protein also provides nuclear retention activity which permits a more stringent assessment of nuclear export.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro, certain recombinant versions of NMD3 possess a very high affinity for CRM1 (40), ϳ100-fold higher than regular NESs. To test whether the export defect due to depletion of Nup214-Nup88 was specific for high affinity NESs, we determined the nuclear export driven by an NES of a similar affinity, the supraphysiological S1 NES (44). Depletion of Nup214-Nup88 did not induce nuclear accumulation of this reporter protein, indicating that the effects were not related to high affinity CRM1 binding of NMD3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the fact that both CSR and stability require maintenance of key hydrophobic positions in the NES and show a similar dependence on the identity of the interdigitating hydrophilic residues suggests that they might both depend on the quality of the AID-exportin interaction. Changes in the hydrophilic interdigitating amino acids in an NES have been shown in other systems to affect the quality of exportin-binding and kinetics of intracellular transport (20,21). The dependence of CSR and protein stability on the nature of the NES could therefore simply reflect a requirement for particular kinetics of nucleocytoplasmic shuttling.…”
Section: Discussionmentioning
confidence: 99%
“…However, Engelsma et al (29) identified NES-like peptides from a pool of randomly generated synthetic peptides, that exhibited a marked nuclear envelope accumulation in permeabilized HeLa cells. These synthetic NESs showed unusually strong interaction with Crm1, leading to their description as "supraphysiological" (29). These results led us to consider that the NPC localization of the Nmd3 mutant proteins may similarly depend on increased binding to Crm1.…”
Section: Accumulation Of Mutant Nmd3mentioning
confidence: 99%